The marriage metaphor in Hosea 2:4-17 against its ancient Near Eastern background - Kruger, Paul Albertus 1948- (1992)
In this contribution it is illustrated that a background knowledge of the juridical principles governing the ancient Near Eastern marriage institution is essential for the proper comprehension of certain aspects of the marriage metaphor in Hosea 2:4-17. It is further shown that there is a logical progression in the presentation of the figurative details of this metaphor. The aspects treated are the hostile confrontation and the so-called divorce formula (2:4a), the exposure of the wife's nakedness (2:5a), the provision of her sustenance (2:7b), the termination of the marriage bond (2:11-12), the bridal gifts (2:10,17) and the answer of the bride (2:17b).
Keywords: Divorce formula; Hosea; Hostile confrontation; Juridical principles; Marriage metaphor; Near Eastern background; Religious-historical context; Symbolic acts; Verba solemnia